2010
DOI: 10.1016/j.alcohol.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ethanol-induced ocular abnormalities in mice through dietary administration of N-acetylcysteine

Abstract: N-acetylcysteine (NAC) is a derivative of the amino acid L-cysteine that previously has been shown to protect against ethanol (EtOH)-induced apoptosis during early development. Ongoing research is demonstrating that NAC is also proving clinically beneficial in reducing oxidative stress-mediated lung, liver and kidney damage, with protection likely resulting from a NACmediated increase in glutathione levels. In the present study, the hypothesis that co-administration of NAC and EtOH via liquid diet on days 7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…As mentioned above, NAP and SAL are also believed to mitigate the teratogenecity of alcohol partly through reducing oxidative stress (Spong, et al 2001). Parnell et al (2010) recently reported that dietary administration of N-acetylcysteine (NAC), which is known to reduce oxidative stress, mitigated alcohol's teratogenecity. Similarly, vitamin E and beta-carotene supplementation have been found to reduce alcohol-induced damage (Mitchell et al 1999).…”
Section: Antioxidantsmentioning
confidence: 99%
“…As mentioned above, NAP and SAL are also believed to mitigate the teratogenecity of alcohol partly through reducing oxidative stress (Spong, et al 2001). Parnell et al (2010) recently reported that dietary administration of N-acetylcysteine (NAC), which is known to reduce oxidative stress, mitigated alcohol's teratogenecity. Similarly, vitamin E and beta-carotene supplementation have been found to reduce alcohol-induced damage (Mitchell et al 1999).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Fetal alcohol exposure has been shown to lead to an increase in lipid peroxidation in the brain and liver (Chen et al, 1997). There have been several studies documenting the use of antioxidants or ROS-clearing enzymes to decrease the rates of alcohol-induced malformations (Chen et al, 2004; Shirpoor et al, 2009; Patten et al, 2013; Parnell et al, 2010). However, others have noted that the corresponding decrease in oxidative stress and apoptosis may not be sufficient to correct some neurological disorders caused by prenatal alcohol exposure (Marino et al, 2004).…”
Section: Intersection Of Upr Apoptosis and Oxidative Stress In Dmentioning
confidence: 99%
“…N-acetylcysteine is an antioxidant that crosses the placenta and has previously been shown to inhibit oxidative stress during pregnancy. [56][57][58][59][60] In the current study, the hypoxic fetal guinea pig liver exhibits histopathological damage, increased lipid peroxidation, and DNA fragmentation.…”
Section: Effect Of Nac On Hypoxia Responsesmentioning
confidence: 99%